Analisis Manajemen Logistik Obat di Instalasi Farmasi BLUD Rumah Sakit Benyamin Guluh Kabupaten Kolaka Tahun 2024 - Taqiyah Hafidzah; Agnes Mersatika Hartoyo (Jurnal Kendari Kesehatan Masyarakat, 2024)
Drug logistics management in hospitals is crucial, encompassing planning, procurement, storage, distribution, and elimination stages that are interconnected. At BLUD Benyamin Guluh Hospital in Kolaka Regency, there are issues with drug supply shortages in the Pharmaceutical Installation. This study aimed to analyze the drug logistics management process at the hospital. Using qualitative methods, including in-depth interviews and observation, the results showed several key findings. Human resources in the pharmacy have not received adequate and consistent training. The drug budget comes from BLUD funds, and drug planning follows the consumption method, though there are challenges due to unavailable supplies from distributors. Drug procurement occurs every three months, based on the e-catalog list. Storage is organized alphabetically and by dosage form, using FIFO and FEFO methods. Distribution is based on requests from hospital units. However, drug maintenance is not specifically conducted; upon arrival, supplies are checked for damage. Control is carried out regularly through stock-taking. For drug elimination, expired or damaged inventory is recorded and written up for disposal. Overall, despite these challenges, the drug availability at BLUD Pharmacy Installation is sufficient to meet the hospital’s needs for a year. This analysis highlights that while the drug logistics system functions relatively well, addressing training gaps and improving procurement processes would enhance the overall efficiency of the hospital’s pharmaceutical operations